GAMBARAN FAKTOR – FAKTOR KEJADIAN LESI PRAKANKER LEHER RAHIM DI PUSKESMAS CANDIROTO, KABUPATEN TEMANGGUNG - Chasanah, Mazroatul; Udiyono, Ari; Saraswati, Lintang Dian; Suwandono, Agus (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Cervical cancer is a leading cause of mortality and morbidity after breast cancer, representing approximately 12% of all cancer in women worldwide. Early diagnostic of cervical cancer with cervical precancerous lesions. The aim of the study is to describe the incidence of precancerous cervical lesions in Puskesmas Candiroto, Temanggung Regency. The study is an observational study which uses case control approach. Population of the study are woman who has conducted VIA test in Puskesmas Candiroto in 2015 – 2016 with 120 respondents. Analysis using frequency distribution. The result of distribution shows that Offspring history has 10,0% in the control grup, education has 38,0% with elementary school, using hormonal contraception (injection) has 40% in case group and marriage under 20th has 49,2% in control group . it is suggest that women must using non hormonal contraception and keep her hygiene personal.